2023
DOI: 10.3389/fimmu.2023.1197152
|View full text |Cite
|
Sign up to set email alerts
|

PANoptosis-based molecular subtyping and HPAN-index predicts therapeutic response and survival in hepatocellular carcinoma

Fei Song,
Cheng-Gui Wang,
Jia-Zhen Mao
et al.

Abstract: BackgroundHepatocellular carcinoma (HCC) is a highly prevalent and fatal cancer. The role of PANoptosis, a novel form of programmed cell death, in HCC is yet to be fully understood. This study focuses on identifying and analyzing PANoptosis-associated differentially expressed genes in HCC (HPAN_DEGs), aiming to enhance our understanding of HCC pathogenesis and potential treatment strategies.MethodsWe analyzed HCC differentially expressed genes from TCGA and IGCG databases and mapped them to the PANoptosis gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“…Meanwhile, 277 PANoptosis-related genes were identified from the published literature by merging the gene lists of apoptosis, necroptosis and pyroptosis while removing redundant genes. 16 Finally, DEGs were intersected with PANoptosis-related genes to obtain SPAN_DEGs.…”
Section: Methodsmentioning
confidence: 99%
“…Meanwhile, 277 PANoptosis-related genes were identified from the published literature by merging the gene lists of apoptosis, necroptosis and pyroptosis while removing redundant genes. 16 Finally, DEGs were intersected with PANoptosis-related genes to obtain SPAN_DEGs.…”
Section: Methodsmentioning
confidence: 99%
“…An increasing number of studies have reported a role for PANoptosis in the malignant biological behaviour and evolution of cancer and on the influence on tumour responses to immunotherapy [ 11 13 ]. Additionally, recent studies have demonstrated that PANoptosis-based molecular subtyping is helpful in determining the prognosis and therapeutic response of HCC [ 14 , 15 ], providing a basis for individualised precision therapy [ 16 ]. Hence, the exploration of the molecular mechanisms of PANoptosis in HCC has implications for broadening the diagnostic and therapeutic options presented for HCC.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, understanding the unique mechanisms of PANoptosis in HCC is vital for predicting treatment responses and developing personalized treatment plans. Given the central role of PANoptosis in the pathogenesis of HCC, in-depth research in this area is crucial for the development of new diagnostic biomarkers and therapeutic targets [14]. Tis will not only help elucidate the pathophysiological mechanisms of HCC but may also lead to more efective treatment modalities, thereby improving clinical outcomes for patients.…”
Section: Introductionmentioning
confidence: 99%